Progressive recovery of a tropical deforested stream community after a flash flood - Marques, Lucas Cerqueira [UNESP]; Ceneviva-bastos, Mônica [UNESP]; Casatti, Lilian [UNESP] (Associação Brasileira de Limnologia, 2013)
AIM: In this study, we evaluated and compared community attributes from a tropical deforested stream, located in a pasture area, in a period before (PRED I) and three times after (POSD I, II, and III) a flash flood, in order to investigate the existence of temporal modifications in community structure that suggests return to conditions previous to the flash flood. METHODS: Biota samples included algae, macrophytes, macroinvertebrates, and fish assemblages. Changes in stream physical structure we also evaluated. Similarity of the aquatic biota between pre and post-disturbance periods was examined by exploratory ordination, known as Non-Metric Multidimensional Scaling associated with Cluster Analysis, using quantitative and presence/absence Bray-Curtis similarity coefficients. Presence and absence data were used for multivariate correlation analysis (Relate Analysis) in order to investigate taxonomic composition similarity of biota between pre and post-disturbance periods. RESULTS: Our results evidenced channel simplification and an expressive decrease in richness and abundance of all taxa right after the flood, followed by subsequent increases of these parameters in the next three samples, indicating trends towards stream community recovery. Bray-Curtis similarity coefficients evidenced a greater community structure disparity among the period right after the flood and the subsequent ones. Multivariate correlation analysis evidenced a greater correlation between macroinvertebrates and algae/macrophytes, demonstrating the narrow relation between their recolonization dynamics. CONCLUSIONS: Despite overall community structure tended to return to previous conditions, recolonization after the flood was much slower than that reported in literature. Finally, the remarkably high flood impact along with the slow recolonization could be a result of the historical presence of anthropic impacts in the region, such as siltation, riparian forest complete depletion, and habitat simplification, which magnified the effects of a natural disturbance.

OBJETIVO: Neste estudo, foram avaliados e comparados os atributos de uma comunidade de riacho no Brasil em um período anterior (PRED) e três posteriores (POSD I, II e III) a uma enchente repentina, a fim de investigar a existência de modificações temporais na estrutura da comunidade que sugira retorno às condições anteriores à enchente. MÉTODOS: Amostras da biota incluíram algas, macrófitas, macroinvertebrados e peixes. Alterações na estrutura física do riacho também foram avaliadas. A similaridade da biota aquática entre os períodos pré e pós-distúrbio foi examinada por ordenação exploratória, conhecida como Análise de Escalonamento Multidimensional Não Métrico com Cluster, utilizando os coeficientes de similaridade de Bray-Curtis quantitativo e de presença/ausência. Dados de presença e ausência foram usados para análise de correlação multivariada (Relate Analysis) a fim de investigar a similaridade da composição taxonômica entre os períodos pré e pós-distúrbio. RESULTADOS: Houve uma diminuição do canal do riacho e expressivo decréscimo na riqueza e abundância de todos os táxons logo após a enchente, seguido por aumentos subsequentes nas três próximas amostragens, indicando uma tendência em direção à recuperação da comunidade de riacho. Os coeficientes de Bray-Curtis evidenciaram grande disparidade na estrutura da comunidade entre o período imediatamente após o distúrbio e os subsequentes. A análise de correlação multivariada demonstrou forte correlação entre macroinvertebrados e algas/macrófitas, indicando estreita relação entre a dinâmica de recolonização desses grupos. CONCLUSÕES: Apesar da estrutura da comunidade indicar retorno às condições iniciais, a recolonização foi muito mais lenta em relação aos registros da literatura. Finalmente, o forte impacto da enchente, somado à recolonização lenta, podem ser o resultado da presença histórica de interferências antrópicas na região, como assoreamento, destruição completa da vegetação ripária e simplificação do hábitat, que amplificaram os efeitos de um distúrbio natural.
Recuperação gradual de uma comunidade de riacho tropical desflorestado após enchente repentina
Keywords: distúrbio; enchentes erosivas; recolonização; macroinvertebrados; macrófitas; peixes; Disturbance; erosive floods; recolonization; macroinvertebrates; Macrophytes; Fish